Warped Product Pseudo-Slant Submanifolds of a Nearly Cosymplectic Manifold - Siraj Uddin; Bernardine R. Wong; A. A. Mustafa (Abstract and Applied Analysis)
We study warped product pseudo-slant submanifolds of a nearly cosymplectic manifold. We obtain some characterization results on the existence or nonexistence of warped product pseudo-slant submanifolds of a nearly cosymplectic manifold in terms of the canonical structures 𝑃 and 𝐹.